Redescription of Pulvinaria indica Avasthi & Shafee, 1985 (Hemiptera: Coccomorpha: Coccidae) with new host and distribution records - Joshi, Sunil; Ramya, R.s.; Navik, Omprakash; Pawar, S.a.; Hole, U.b.; Tambe, A.b. (Zootaxa, 2019)
The soft scale Pulvinaria indica (Hemiptera: Coccomorpha: Coccidae) was described by Avasthi & Shafee in 1985 from four females collected on Duranta repens Linn. from Simhachalam, Visakhapatnam, Andhra Pradesh, India. The original description, however, was scanty and attempts to locate the type material were unsuccessful. To facilitate the identification and separation of P. indica from other similar species, we redescribe and illustrate the adult female, based on newly collected specimens found on an economically important new host plant. Management options in the event of its future occurrence are discussed briefly.